Evidence of physical activity interventions on non-motor symptoms of people with Parkinson’s disease: an umbrella review - Moratelli J.A.* (2024)
© The Author(s), under exclusive licence to Springer-Verlag Italia S.r.l., part of Springer Nature 2024.Background: The aim of this umbrella review was to synthesize evidence from physical activity interventions on non-motor symptoms of people with Parkinson’s disease (PD), as well as to assess the quality of systematic reviews and meta-analyses included. Methods: The Pubmed, Cochrane Library, Web of Science, ScienceDirect and SCOPUS databases were searched for systematic reviews and meta-analyses that should investigate any type of physical activity in depression, anxiety, mood, sleep disturbances, and cognitive impairment in people with PD. Methodological quality was assessed using AMSTAR. Results: Twenty systematic reviews met the criteria; most studies were classified as high quality. Strong evidence has shown that different types of physical exercise promote positive results in PD. Most interventions investigated the effects of aerobic exercise and complementary practices, with great emphasis on symptoms of depression and cognition. However, the frequency and duration of these interventions are unclear. Conclusion: In general, this review suggests that the practice of physical activity should be included as a form of rehabilitation and combined with drug treatment in people with PD.